Unusual findings of acute myeloid leukemia with inv(3)(q21q26.2) or t(3;3)(q21;q26.2): A multicenter study. (22nd February 2019) - Gong, Xubo; Yu, Teng; Tang, Qiusu; Fu, Yanbiao; Wu, Jie; Zhu, Yongze; Tu, Hongxiang; Ge, Haifeng; Lu, Xingguo; Gong, Donghua; Zhao, Xiaoying
Abstract: Introduction: AML with inv(3)(q21.3q26.2) or t(3;3)(q21.3;q26.2) [inv(3)/t(3;3)] was very rare. Currently, most reports of AML‐inv(3)/t(3;3) were from Western countries, and few reports were from Asian countries. Racial differences in patients with AML‐inv(3)/t(3;3) are still unknown. Methods: Between January 1996 and April 2018, a total of 37 AML cases with inv(3)/t(3;3) were studied retrospectively. They were collected from 2229 primary AML cases performed with conventional cytogenetic analysis (37/2229, 1.66%). Results: Here, some differences were found by comparing our data with those from Western countries. In our series, AML with inv(3)(q21q26) had a lower incidence than that with t(3;3)(q21;q26) (11 vs 26 cases). Our patients seemed to be more younger (median, 43 years) and have lower hemoglobin concentrations (median, 73 g/L) and higher platelet count (median, 351 × 10 9 /L). A higher incidence of acute monoblastic and monocytic leukemia (45.9%) was observed in our patients. Immunophenotypic studies showed that CD38 (30.8%) was not so frequently expressed as that in the earlier reports. Mutations analysis showed a high frequency of NRAS mutations (45.0%), followed by SF3B1 (15.0%), GATA2 (15.0%), FLT3‐ITD (10.0%), C‐Kit/D816 (5.0%), and CEBPA (5.0%), without mutation of NPM1(Exon12) or JAK2V617 . Conclusion: Ethnic differences do exist between the Chinese and Western patients with AML‐inv(3)/t(3;3), and more attention should be paid involving different ethnic populations and geographic regions.